WEB PORTAL - Mr. C.U. Chauhan; Ms. Shivani Parate; Ms. Vaidehi Burbure; Mr. Adarsh Pawar; Mr. Nihar Gundawar; Mr. Aniket Nagdeve (International Journal of Innovations in Engineering Research and Technology, 2021)
A web site is a specially designed Web page that brings information together from a variety of sources in the same way. The web site will enable the user to access data. About various services such as finding accommodation, restaurants, and entertainment in the corresponding area and contact the educational forum, and find friends online. Information provided to Customers will be protected using Standard Encryption Algorithms such as the Advanced Encryption Standard (AES). Through this System, we will provide updates to our members regarding the latest changes to any information the user is interested in. At the discretion of the viewer or member he or she can filter the details according to his or her desired location and budget or he or she can create a Wish list of accommodation and restaurants for updates on them.